Factors Associated with Hygiene Practices in Menstrual Management - Upadhya Adhikari, Shanta; Adhikari, Surya Prasad (ILAM इलम, 2026)
Menstrual hygiene management is a key indicator to reducing the vulnerability of girls and women to reproductive tract infections. The main aim of this study is to examine the menstrual hygiene practices, and management. This study is based on a quantitative research design with census method, utilizing a self-administered, questionnaire among all eligible adolescent girls (grade 6-10) across eight community schools in Kirtipur Municipality of Kathmandu district. The sample size was determined based on the availability of all eligible girls from selected community schools of grades six to ten of eight community schools of Kirtipur Municipality. This study reflects encouraging progress in menstrual hygiene practices. Most of the respondents (98 %) reported they were frequently changing their pads for maintaining menstrual hygiene management and preventing infections. Furthermore, the fact that 87 percent of respondents acknowledged receiving institutional support, such as free sanitary pads and related facilities. However, more than half percent (51%) respondents reported that an inadequate supply of clean water at schools undermines the ability to maintain proper hygiene, management particularly handwashing after changing pad, daily bathing.